Prognostic determinants and functional role of PIK3C2G in stage IIb-IIIa lung adenocarcinoma: insights from clinical and molecular analyses - Gao, Chao; Zhang, Jiaqi; Du, Xin; Gao, Xuehan; Diao, Xiayao; Zhao, Ke; Chen, Yeye; Li, Shanqing (Frontiers in Oncology, 2025)
BackgroundTo investigate the prognostic factors for stage IIb and IIIa lung adenocarcinoma following radical surgery and to explore the molecular mechanisms underlying these prognostic markers, focusing on the role of PIK3C2G.MethodsA retrospective analysis of patients with stage IIb or IIIa lung adenocarcinoma who underwent radical surgery between January 2017 and June 2023 was conducted. Baseline clinical and pathological data, surgical methods, and postoperative treatments were analyzed to assess overall survival (OS). Univariate and multivariate Cox regression analyses were conducted to identify prognostic factors. Whole-exome sequencing (WES) was performed on a subset of the patients with preserved tumor tissues and no matched targeted therapies to identify high-frequency mutated genes. Functional experiments in A549 lung adenocarcinoma cells were performed to evaluate the role of the significant genes in tumor progression through cell proliferation, migration, invasion, apoptosis, and cell cycle assays.ResultsThe survival analysis of 877 stage IIb and IIIa lung adenocarcinoma cases revealed significant differences in clinical characteristics and outcomes. Stage IIb patients had a median OS of 58 months compared to 37 months for stage IIIa, with 5-year OS rates of 46.9% and 30.5%, respectively. Univariate and multivariate Cox regression identified pathological stage, number of positive lymph nodes, age, and targeted therapy as independent prognostic factors. WES of 184 patients with no matched targeted therapies revealed high-frequency mutations in genes such as TP53 and PIK3C2G, with the latter emerging as the most significant prognostic marker. Functional assays demonstrated that the knockdown of PIK3C2G in A549 cells significantly reduced proliferation, migration and invasion while promoting apoptosis and disrupting cell cycle progression.ConclusionPIK3C2G was identified as a significant prognostic marker in stage IIb and IIIa lung adenocarcinoma, with functional data supporting its therapeutic potential. Taken together, this study integrates clinical and molecular findings, which could be used as a reference to guide personalized treatment strategies.